Reservoir Characteristics of the Lower Miocene Carbonate Formations in Kor Mor Gasfield, Kirkuk Area, NE Iraq - Fouad M. Qader; Shabaz M. Ali (Tikrit Journal of Pure Science)
This paper presents the evaluations of the reservoir characterization of the Lower Miocene Euphrates, and Jeribe carbonate formations selected for this study in Kor Mor Gasfield in Northeastern Iraq. The thickness of Euphrates ranges between 30 and 65m, and Jeribe between 30 and 50m in this field. They are overlain by a thick evaporate cap rock of the Fatha Formation. The two formations are separated by the thin evaporate rock unit of the Dhiban Formation. The full set of log data for the well Km-9 was used in addition to some general data derived from other eight wells (Km-1 to Km-8). The log data was used in evaluating the reservoir properties of the two rock units. The detected lithologies from the available mud log and well reports showed that the two formations, mostly dolostone and dolomitic limestone, were dominated. From the log data, different reservoir properties including clay content, clay types, porosity, and fracture index were estimated. The average porosity of the Euphrates reservoir was around 0.15 and that of the Jeribe was about 0.10. The secondary porosity made a significant fraction of porosity in both units.